Fibrinogen-Like Protein 1 as a Novel Biomarker of Psoriasis Severity - Sun X; Liu L; Chen S; Wang J; Cai X; Song J; Zhou M; Guo D; Kuai L; Ding X; Li B; Li X (Dove Medical Press, 2022)
Xiaoying Sun,1,2 Liu Liu,1,2 Siting Chen,1,2 Jiao Wang,1,2 Xiaoce Cai,1,2 Jiankun Song,3 Mi Zhou,1,2 Dongjie Guo,1,2 Le Kuai,1,2 Xiaojie Ding,1,2 Bin Li,2,4 Xin Li1,2 1Department of Dermatology, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China; 2Institute of Dermatology, Shanghai Academy of Traditional Chinese Medicine, Shanghai, People's Republic of China; 3Dermatology of TCM, Shanghai Skin Diseases Hospital, Shanghai, People's Republic of China; 4Department of Dermatology, Shanghai Skin Diseases Hospital, Shanghai, People's Republic of ChinaCorrespondence: Xin Li, Department of Dermatology, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, 110 Ganhe Road, Hongkou District, Shanghai, 200437, People's Republic of China, Tel +8613661956326, Email 13661956326@163.com Bin Li, Institute of Dermatology, Shanghai Academy of Traditional Chinese Medicine, 110 Ganhe Road, Hongkou District, Shanghai, 200437, People's Republic of China, Tel +8618930568129, Email 18930568129@163.comBackground: Psoriasis is an immune-mediated chronic systemic inflammatory skin disease whose diagnosis and severity assessment pose challenges for clinicians worldwide. The use of serum biomarkers facilitates the early diagnosis and treatment of psoriasis.Methods: This case-control study compared tumor necrosis factor α (TNF-α), interleukin (IL)-6, IL-17, IL-10, and fibrinogen-like protein 1 (FGL1) levels of 139 untreated psoriasis patients and 140 healthy controls. Serum samples were collected, and enzyme-linked immunosorbent assays were performed to quantify their levels. Subgroups were analyzed according to abnormal lipid metabolism status.Results: Compared to controls, patients with psoriasis exhibited lower concentrations of serum TNF-α, IL-17, and FGL1 (P < 0.05). A correlation analysis showed that FGL1 was inversely correlated with high-density lipoprotein cholesterol and IL-17 in the psoriatic state. Stepwise multiple regression analysis revealed that FGL1 and total cholesterol were the independent determinants of Psoriasis Area and Severity Index (PASI) score in psoriasis patients. The area under the receiver operating characteristic curve of FGL1 assessing moderate-to-severe psoriasis and mild psoriasis was 0.70, while the area under the curve (AUC) assessing severe psoriasis and mild-to-moderate psoriasis was 0.67, better than that of IL-17. In addition, FGL1, but not IL-17, was able to identify psoriasis with abnormal lipid metabolism to a certain extent (AUC = 0.60).Conclusion: In conclusion, serum FGL1 may be a promising biomarker for diagnosing and staging psoriasis. It may also be involved in its progression and comorbid abnormal lipid metabolism.Keywords: psoriasis, disease severity, biomarker, fibrinogen-like protein 1, lipid metabolism